2012
DOI: 10.1039/c2jm30804e
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and mechanically stable antireflective coatings from nanoporous organically modified silica colloids

Abstract: We report the preparation of flexible and mechanically stable antireflective organically modified silica (ormosil) coatings at ambient conditions. Thin films are obtained from colloidal suspensions of ormosil gels which are prepared using methyltrimethoxysilane (MTMS) and tetraethyl orthosilicate (TEOS) monomers. The ormosil suspensions are directly applicable and suitable for the large-area deposition of nanoporous ormosil thin films. The nanoporosity of the films can be tuned by changing the monomer ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 36 publications
1
34
1
1
Order By: Relevance
“…47,48 The phase separation in the gels can be decreased by using some additional tetra-functional monomers such as TMOS and TEOS. 28,49 Accordingly, ormosil colloids with smaller grains can be obtained from these less phase separated gels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 The phase separation in the gels can be decreased by using some additional tetra-functional monomers such as TMOS and TEOS. 28,49 Accordingly, ormosil colloids with smaller grains can be obtained from these less phase separated gels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results revealed that the grain size distribution of ormosil colloids highly depended on the amount of MTMS monomer used in gel synthesis. 28 It is well-known that trifunctional MTMS monomer (i.e., it contains three hydrolyzable methoxy and one nonhydrolyzable methyl ligands) induces phase separation in gels due to low solubility of cyclic and cage-like structures formed during polymerization. 47,48 The phase separation in the gels can be decreased by using some additional tetra-functional monomers such as TMOS and TEOS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Very small colloids (<30 nm), such as organically modified silica (ORMOSIL) particles, can be used to generate uniform antireflective coatings, but typically require the addition of stabilizing elements to make robust films. [198][199][200] Larger colloids can be used, with or without other materials, to generate hierarchically structured materials with very high transmission values. 188,201,202 Figure 9 shows an example of such a structure created by using a monolayer of colloids as an etch mask to make a grating structure on which a disordered array of gold nanoparticles is created.…”
Section: Factors Affecting Optical Applicationsmentioning
confidence: 99%
“…[12][13][14][15] However, they are inefficient in terms of angle-dependence and are feasible only for narrowband applications. Therefore, anti-reective structures (ARSs) are essential for optical devices, solar cells, light emitting diodes (LEDs), and displays in order to prevent undesired reection.…”
Section: -11mentioning
confidence: 99%